Silicon Solar Cells: Conductive Hole‐Selective Passivating Contacts for Crystalline Silicon Solar Cells (Adv. Energy Mater. 16/2020). Issue 16 (28th April 2020) - Wan, Lu; Zhang, Cuili; Ge, Kunpeng; Yang, Xueliang; Li, Feng; Yan, Wensheng; Xu, Zhuo; Yang, Lin; Xu, Ying; Song, Dengyuan; Chen, Jianhui
Abstract : In article number 1903851, Jianhui Chen and co‐workers discern a region of good conductivity and passivation in a passivation‐conductivity phase‐like diagram, which enables conductive passivating contacts for silicon solar cells. This work suggests a low‐cost surface engineering strategy for future photovoltaic technologies, with the advantage of omitting the use of conventional dielectric passivation materials and simplifying the fabrication process.